PENINGKATAN KREATIVITAS BELAJAR MATEMATIKA MELALUI PENDEKATAN KONTEKSTUAL (CTL) - Dewi Azizah (LPPM Universitas Pekalongan, 2012)
The purposes of the research were, first, to increase the students’ creativity of learning mathematic and, second, to improve students’ learning achievement by using contextual approach. The research was a collaborative achievement research between the writer, the mathematic teacher and headmaster. The subject of the research were the eighth grade student of SMP Muhammadiyah 10 Surakarta. The qualitative descriptive data were than analyzed through the use of alur method. The results showed the contextual approach could improve the students’ creativity and achievement significantly. The students’ creativity got improved ≥65% and students’ achievement rose from 48.1% to 68.9%. Keywords: creativity, contextual, achievement